Serum C-reactive protein concentrations in Nova Scotia Duck Tolling Retrievers with immune-mediated rheumatic disease - Hanna Dorotea Bremer; Anna Hillström; Malin Kånåhols; Ragnvi Hagman; Helene Hansson-Hamlin (Acta Veterinaria Scandinavica, 2017)
Abstract Nova Scotia Duck Tolling Retrievers (NSDTRs) are a dog breed often affected by immune-mediated rheumatic disease (IMRD), a disorder characterised by chronic stiffness and joint pain. Most, but not all, dogs with IMRD, have antinuclear antibodies (ANA), which are also commonly present in the autoimmune disease systemic lupus erythematosus (SLE). The clinical and diagnostic findings of IMRD indicate that it is an SLE-related disorder. C-reactive protein (CRP), an acute phase protein, is a quantitative marker of inflammation for many diseases and is used for diagnosing and monitoring systemic inflammation in both humans and dogs. However, in human SLE, CRP concentrations are often elevated but correlate poorly with disease activity; they can be low in individual patients with active disease. The aim of the study was to investigate CRP in a group of NSDTRs with the SLE-related disorder IMRD. The hypothesis was that CRP concentrations would be increased in dogs with IMRD compared to healthy dogs, but that the increase would be mild. Serum CRP concentrations were measured in 18 IMRD-affected NSDTRs and 19 healthy control NSDTRs using two different canine-specific CRP assays. Dogs with IMRD and ANA had higher CRP concentrations than the control dogs, but the concentrations were below the clinical decision limit for systemic inflammation for most of the IMRD dogs. These results indicate that CRP concentrations were increased in dogs with IMRD and ANA, but the increase was mild, similar to what has been observed in human SLE.